TV Series in a Big City: Geo-Poetics of Telenovelas 1980s—2020s - L. S. Kislova; T. N. Ratsen; S. O. Dracheva (Научный диалог)
The article explores the influence of toponymic images on the aesthetics of popular foreign and Russian television Series. The television series is a specific artistic model, the transformation and functioning of which is the result of significant television influence on the audience. Its uniqueness lies in the fact that, being a key genre of contemporary mass culture on one hand, and a multimedia text on the other, the series allows visual content to displace verbal content and constructs a certain reality in the minds of viewers. Within the framework of the geopoetic approach, the authors of the article examine the image of the city in television projects from different years, analyze the functions of urban signs and symbols, and identify various artistic techniques used to characterize characters and represent national-cultural spaces. Special attention is given to the role of the city as a setting and a tool for plot development in TV shows. The result of the study is the identification of the dynamics of the city image in television projects from the 1980s to the 2020s, which allows us to characterize television Series not only as a source of entertainment, but also as a social and national project that claims one of the dominant positions in contemporary culture.